56.5k views
1 vote
B/13-3b/13=8/13 help please

1 Answer

5 votes

(b)/(13) -
(3b)/(13) =
(8)/(13)
Since the two fractions have a common denominator already, we can just subtract the numerators.
b-3b=-2b or -3b+b=-2b
Either way you get the same answer :)
Our new fraction is
(-2b)/(13)
Now we know that this must be equal to
(8)/(13)
Again, since the denominators are already the same of course they are equal. 13=13
Now we have to set the numerators equal
-2b=8
Use inverse operations to get b alone
-2b=8
÷-2 ÷-2
b=-4
If you have any questions, feel free to ask. Hope this helped! :)

User Rosco
by
7.8k points

No related questions found